2014
DOI: 10.1007/978-3-319-11215-2_25
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Distance Estimation in a CAVE

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. Abstract. Past studies have shown consistent underestimation of distances in virtual reality, though the exact causes remain unclear. Many virtual distance cues have been investigated, but past work has failed to account for the possible addition of cues from the physical environment. We describe two studies that assess users' performance and strategies when ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Even if the observer looks at an object on the ground 2m away entirely using eye rotation, not head rotation, that would only lead to a displacement of the horizon by 4mm in a CAVE display (the same displacement upwards as the downwards displacement of the nodal point). Since the distance underestimation of objects on the ground-plane is still reported in CAVE environments [Marsh et al 2014], this indicates that the gaze-contingent distortions identified in this paper cannot account for this distance underestimation.…”
Section: Mitigating Gaze-contingent Distortionsmentioning
confidence: 67%
“…Even if the observer looks at an object on the ground 2m away entirely using eye rotation, not head rotation, that would only lead to a displacement of the horizon by 4mm in a CAVE display (the same displacement upwards as the downwards displacement of the nodal point). Since the distance underestimation of objects on the ground-plane is still reported in CAVE environments [Marsh et al 2014], this indicates that the gaze-contingent distortions identified in this paper cannot account for this distance underestimation.…”
Section: Mitigating Gaze-contingent Distortionsmentioning
confidence: 67%
“…An interesting phenomenon is the differences that exist between HMDs and LIPDs, either using immersive walls [21], [17]) or CAVE systems ( [16], [13], [2]). We can highlight 3 important aspects about LIPDs on these studies: (1) underestimation effects seem to be less stronger than in HMDs, (2) the physical space between the user and the projection screen is the most important factor and, (3) the effects are asymmetric with underestimation for objects at positive stereoscopic parallax and slight overestimation with objects at zero or negative stereoscopic parallax.…”
Section: Distance and Size Perception In Vrmentioning
confidence: 99%
“…One commonly reported example is underestimation of virtual distances relative to equivalent distances in the physical world [4]. These biases might relate to impoverished graphical cues, interface attributes such as locomotion effort [9], or incidental characteristics of the physical display technology such as optical accommodation [3] or salient borders [6].…”
Section: Perceptual Biasesmentioning
confidence: 99%
“…First, biases affect judgements of the CAVE walls (VW 1 ) as seen from within the PE, because judgements in the physical world are not always accurate. As users consider physical relationships when perceiving virtual distances [6], for example, inaccurate physical judgements may also affect virtual judgements. Biases in viewing VE 1 through VW 1 , due to display characteristics such as field of view or resolution, may affect a user's judgements in VR.…”
Section: Tracing the Sources Of Biasmentioning
confidence: 99%